Catenary mechanism in steel columns under extreme lateral loading: A basis for building progressive collapse analysis - Foad Kiakojouri; Valerio De Biagi (Developments in the Built Environment)
The studies on progressive collapse have primarily focused on threat-independent methods, wherein a sudden column removal is suggested in codes. However, a real collapse scenario is necessarily threat-dependent. Focusing on blast- and impact-induced progressive collapses, the current study considers cases in which damage is concentrated in a single member, without resulting in complete column loss. It is demonstrated that the progressive collapse performance under specific threats can be better or worse compared to that of sudden column removal. Thus, dynamic column removal does not necessarily guarantee the most critical scenario, as the response in a damaged system can sometimes exceed expectations. A simple analytical model is proposed to describe in detail the observed phenomena and emphasizes the development of catenary forces in the column under lateral extreme loading scenarios. The results provide a deeper insight into the progressive collapse performance of frame systems and the involved member-level resisting mechanisms.